Menelisik Kronologi Surah dalam Al-Qur’an Perspektif Neal Robinson - Tinggal Purwanto (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2018)
This paper explored the idea of Neal Robinson in his book, Discovering The Qur'an: A Contemporary Approach To A Veiled Text in order to understand the chronology of surah in the Qur'an. After reading the book, the writer found that there are three strategies to understand the chronology of the surah in the Qur'an; They are investigating the events of occasions of the revelation (asbab an-nuzul), understanding the literature of abrogating and abrogated ayahs (nasikh and mansukh), and categorizing the traditional lists of Meccan and Madinan surahs (Makiyyah and Madaniyyah). By conducting those ways, Robinson proved that asbab an-nuzul should be treated with extreme caution. Then, in some cases, asbab an-nuzul should be limited in order to determine the chronological order of the Qur’an. After that, nasikh and mansukh are used merely for the purpose of determining the chronological order of the Qur’an and did not highlight certain evolution within a period of revelation. Finally, by analyzing Madaniyah and Makiyah surah, it revealed the certainty of the origin and the list of traditional surah in which there were some differences in the determination of the date among the companions. The differences are due to rivalry in the collection of the Qur'an and wrong isnads done by some companions in order to increase their prestige.